A method for preparing silicon-carbon negative electrode material by embedding lithium vapor into pores for pre-lithiation

The prelithiation and porous carbon negative electrode material coating process is solved through lithium vapor embedded in pores, and the rapidity and efficiency problems in the preparation of silicon carbon negative electrode materials for lithium-ion batteries are significantly improved, and the specific capacity and circulation performance of the battery are extended. Battery lifespan.

CN118684215BActive Publication Date: 2024-12-13GANZHOU RUIFUTE TECHNOLOGY CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411171724.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-13
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

The silicon-carbon negative electrode materials of existing lithium-ion batteries are not fast and simple in preparation. For the first time, Coulomb efficiency is low, and it is easy to generate SEI films, consuming active lithium ions of the positive electrode, resulting in attenuation of the battery capacity.

Method used

The process of prelithiation of lithium vapor embedded pores is adopted to prepare porous carbon negative electrode materials through high-temperature carbonization and activated biomass powder, coat hard carbon and mix with nano-scale silicon powder, and prepare silicon carbon by vacuum liquid phase coating granulation. Negative electrode material improves the specific capacity and cycling performance of the electrode.

Benefits of technology

It significantly improves the specific capacity and first-time Coulomb efficiency of the negative electrode of lithium-ion battery, reduces the attenuation of cycle performance, and improves the service life and market competitiveness of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118684215B_ABST
    Figure CN118684215B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing silicon-carbon negative electrode materials by embedding lithium vapor into pores for pre-lithiation, comprising the following steps: ① preparing micron-sized porous carbon negative electrode materials; ② allowing lithium vapor to be adsorbed in the pores of the prepared micron-sized porous carbon negative electrode materials to obtain pre-lithiation carbon materials; ③ introducing carbon source gas to coat a layer of hard carbon on the surface of the pre-lithiation carbon materials; ④ the obtained carbon-coated pre-lithiation carbon materials and nano-sized silicon powder are subjected to vacuum liquid phase coating granulation and finally carbonization in a certain proportion to obtain silicon-carbon negative electrode materials. The silicon-carbon negative electrode materials prepared by the present invention significantly improve the cycle performance and first coulomb efficiency of the negative electrode materials, and the specific capacity is lower than the normal pre-lithiation attenuation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery electrode materials, and specifically relates to a method for preparing silicon-carbon negative electrode materials by embedding lithium vapor into pores for pre-lithiation. Background Art

[0002] Lithium-ion batteries have the advantages of high capacity, no memory effect, fast reversible charge and discharge, and high Coulomb efficiency. They are now widely used in 3C products, electric vehicles, and energy storage technologies. At present, the commercial negative electrode material graphite for lithium-ion batteries is close to the theoretical capacity of 372 mAh / g, and it is difficult to improve it. The theoretical capacity of silicon is 4200 mAh / g, which is more than ten times that of graphite negative electrode materials. At the same time, compared with graphite negative electrode materials, silicon has a higher lithium deintercalation potential, which can effectively avoid the precipitation of lithium during high-rate charge and discharge, and improve battery safety performance. At present, there is no large-scale production of high-capacity silicon-carbon negative electrode materials on the market, so the development of such high-energy-density silicon-carbon negative electrode materials has broad prospects and plays a great role in improving market competitiveness. In addition to its greater energy density advantage, silicon produces a large volume effect (up to 300%) during the alloying process with lithium, leading to the collapse of the electrode structure and the peeling of active materials, causing the electrode material to lose electrical contact and resulting in rapid capacity decay. In addition, silicon has poor conductivity, and the initial efficiency of silicon-based negative electrode materials is low, which seriously hinders the practical application of pure phase silicon as a negative electrode material for lithium-ion batteries.

[0003] Scientific research shows that controlling the particle size of silicon powder at the nanometer level can effectively reduce the volume expansion effect of silicon, and at the same time its capacity and cycle performance are also better. Silicon in silicon-carbon negative electrode materials, as a high specific energy component, provides higher lithium storage capacity; porous carbon negative electrode materials serve as a matrix, allowing nano-silicon particles to be dispersed in it, alleviating the volume change of silicon when lithium is inserted and removed, and maintaining good electrical contact between the electrodes.

[0004] As mentioned above, the current silicon-carbon negative electrode material preparation is still insufficient in terms of speed and simplicity. At the same time, in the actual application process, due to the low initial coulombic efficiency of the silicon-based negative electrode and the easy generation of SEI film repeatedly, more active lithium ions in the positive electrode are consumed. In order to further improve the total capacity and energy density of the battery and increase the service life of the lithium-ion battery, the present invention uses a process of pre-lithiation by embedding lithium vapor into the pores to add lithium to the inside of the battery to supplement lithium ions before the lithium-ion battery works. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing silicon-carbon negative electrode materials by pre-lithiation by embedding lithium vapor into pores. This method not only significantly improves the specific capacity of the negative electrode of the lithium-ion battery, but also improves the first coulombic efficiency and cycle performance.

[0006] In order to achieve the above object, the present invention specifically adopts the following technical solutions:

[0007] The present invention provides a method for preparing a silicon-carbon negative electrode material by embedding lithium vapor into pores for pre-lithiation, comprising the following steps:

[0008] Step 1: Carbonizing and activating the biomass powder at high temperature to prepare a porous carbon negative electrode material;

[0009] Step 2: introducing lithium vapor into the porous carbon negative electrode material in step 1 under vacuum and high temperature conditions to obtain a pre-lithiated carbon material;

[0010] Step 3: introducing a carbon source gas and a protective gas under high temperature conditions to coat the surface of the pre-lithiated carbon material obtained in step 2 with hard carbon to obtain a carbon-coated pre-lithiated carbon material;

[0011] Step 4: Mix the carbon-coated pre-lithiated carbon material obtained in step 3 with nano-scale silicon powder, a coating agent, and a solvent, evacuate the mixture, perform vacuum liquid phase coating and granulation, and finally carbonize the mixture to obtain a silicon-carbon negative electrode material.

[0012] Furthermore, nano-scale silicon powder and biomass powder are prepared by ball milling, and micron-scale silicon powder and high-quality coconut shell and bamboo are selected as the materials to be ground, respectively. The micron-scale silicon powder is 5N high-purity silicon powder with D50=5 μm, and the ball milling method is dry ball milling, wet ball milling or plasma ball milling. The specific method is: add the zirconium oxide sphere and the material to be ground into the zirconium oxide tank according to the mass ratio (3-10):1 (preferably the mass ratio is 3:1), ball mill under vacuum, rotate forward at 200-800 rpm for 30 minutes, then stand for 5 minutes, reverse at 200-800 rpm for 30 minutes after standing, continue to stand for 5 minutes, and then continue to rotate forward, and repeat this process, and the ground material is obtained after ball milling and separation.

[0013] Furthermore, the biomass in step 1 includes coconut shells and bamboo; the high-temperature carbonization is carbonization at 400-800°C for 4-12 h, and the activation is activation at 800-1000°C for 2-6 h by introducing water vapor / carbon dioxide, preferably at 1000°C for 6 h.

[0014] Furthermore, in step 1, the D50 of the porous carbon negative electrode material is 7-15 μm, the total pore volume is 1-3 cc / g, and the most probable pore diameter is 0.4-0.85 nm; preferably, the D50 is 8 μm, the total pore volume is 1.5 cc / g, and the most probable pore diameter is 0.55 nm.

[0015] Further, the vacuum and high temperature conditions in step 2 are as follows: evacuate to a relative pressure of 0.01 MPa, then introduce protective gas for ventilation, and after ventilation for more than 3 times, evacuate to a relative pressure of 0.01 MPa, raise the temperature to 1000-1400°C, and then evacuate to a vacuum degree of P / P0 of 10 -2 -10 -6 When the micropore ratio is less than 5%, P / P0 is 10 -2 -10 -3 , 5%≤micropore ratio<30%P / P0 takes 10 -3 -10 -4 When the micropore ratio is ≥30%, P / P0 is 10 -5 -10 -6 , P0 is the saturated vapor pressure of lithium; the introduction of lithium vapor is stopped when P / P0 rises to 0.4-0.6.

[0016] Furthermore, the purity of the lithium vapor is not less than 99.95%.

[0017] Furthermore, the carbon source gas in step three includes one or more of ethane, propane, ethylene, propylene, and acetylene; the high temperature condition is 800-1000° C., and the reaction time is 2-5 h.

[0018] Furthermore, the carbon source gas and the protective gas are mixed and introduced, and the volume ratio of the carbon source gas and the protective gas is (10-50): (50-90), and the protective gas is one or more of helium, argon, and neon; preferably 30 parts by volume of acetylene and 70 parts by volume of argon, and the reaction is carried out at a constant temperature of 1000° C. for 3-4 hours.

[0019] Furthermore, in step 4, the D50 of the nano-scale silicon powder is 50-500 nm, preferably 50 nm; the coating agent includes one or two of modified asphalt and stearic acid; the solvent includes one or more of tar, n-hexane, xylene, and tetrahydrofuran; the mass ratio of nano-scale silicon powder to carbon-coated pre-lithiation carbon material is (3-10): (90-97), the coating agent is added in an amount of 3%-8% of the total mass of the nano-scale silicon powder and the carbon-coated pre-lithiation carbon material, and the solvent is added in an amount of 15%-50% of the total mass of the nano-scale silicon powder and the carbon-coated pre-lithiation carbon material. Preferably, the mass ratio of nano-scale silicon powder to carbon-coated pre-lithiation carbon material is 5:95, the coating agent takes 5% of the total mass of the two (modified asphalt 4%, stearic acid 1%), and the solvent takes 20%-30% of the total mass of the two (tar).

[0020] Furthermore, the conditions for the vacuum liquid phase coating granulation in step 4 are: stirring at 60-150 rpm, heating to 400-600°C, and maintaining the constant temperature for 2-6 h, preferably stirring at 75 rpm and maintaining the constant temperature at 600°C for 3-4 h; the conditions for the final carbonization are: heating to 900-1100°C under protective gas protection, maintaining the constant temperature for 5-7 h, preferably maintaining the constant temperature at 1000°C for 6 h.

[0021] Furthermore, the D50 of the obtained silicon-carbon negative electrode material is 8-18 μm.

[0022] The beneficial effects of the present invention are:

[0023] The silicon-carbon negative electrode material obtained by the present invention is prepared by mixing silicon-carbon material and pre-lithiation carbon material. The silicon-carbon material is based on porous carbon negative electrode material, metallic lithium is evenly distributed in the pores, and a complete hard carbon coating layer is formed on its surface. Then, nano-silicon is fixed on the surface of the carbon-coated pre-lithiation carbon material through a second layer of coated amorphous carbon layer. The silicon-carbon negative electrode material prepared by the present invention significantly improves the cycle performance and first coulomb efficiency of the negative electrode material, and the specific capacity is lower than the normal pre-lithiation attenuation.

[0024] The preparation method of the present invention has abundant and extensive raw materials, and the sources of micron-sized silicon powder and carbon source are sufficient and low in price. The obtained silicon-carbon negative electrode material has excellent performance and good market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the structure of the silicon-carbon negative electrode material prepared in an embodiment of the present invention.

[0026] Figure 2 This is the charge and discharge curve of the silicon-carbon material half-cell test in Example 1 of the present invention.

[0027] Figure 3 It is a comparison chart of the cycle test data of Examples 1-3 of the present invention and Comparative Examples 1-2.

[0028] Figure 4 This is an electron microscope image of the silicon-carbon material of Example 1 of the present invention.

[0029] Figure 5 This is an electron microscope image of the silicon-carbon material of Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] Example 1

[0032] 1. Add 5N high-purity polysilicon powder with D50=5 μm and zirconia balls to the zirconia ball mill at a ball-to-material mass ratio of 3:1, and add anhydrous ethanol of equal mass to the polysilicon powder. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes, let stand for 5 minutes, reverse at 500 rpm for 30 minutes after standing, continue to stand for 5 minutes, and then continue to rotate forward, and repeat this process. After ball milling, separate the zirconia balls and silicon powder through a sieve to obtain nano-scale silicon powder with D50=50 nm.

[0033] 2. Take high-quality coconut shells and zirconia balls in a ball-to-material mass ratio of 3:1 and add them to the zirconia ball mill. At the same time, add anhydrous ethanol of the same mass as the coconut shells. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then let it stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward. Repeat this process. After ball milling, separate the zirconia balls and coconut shell powder through a sieve to obtain a biomass powder with D50=10 μm.

[0034] 3. The obtained biomass powder was placed in a carbonization furnace, and argon was used as a protective gas. The temperature was raised to 600°C and kept at a constant temperature for 6 hours for carbonization. Then, it was transferred to an activation furnace, water vapor was introduced, the temperature was raised to 1000°C, and the temperature was kept at a constant temperature for 6 hours for activation to obtain a micron-sized porous carbon negative electrode material (D50 = 8 μm, total pore volume 1.5 cc / g, most probable pore diameter 0.55 nm).

[0035] 4. Place the obtained micron-sized porous carbon negative electrode material into a ceramic reactor, evacuate until the relative vacuum gauge shows -0.01 MPa, introduce argon until the relative vacuum gauge shows 1 atmosphere, stop introducing argon, evacuate again until the relative vacuum gauge shows -0.01 MPa, repeat 3 cycles to complete the gas exchange. Raise the temperature to 1200℃, and evacuate the vacuum in the reactor until P / P0 is 10 -4 (P0 is the saturated vapor pressure of lithium), lithium vapor (purity 99.95%) is slowly and intermittently introduced, and P / P0 slowly increases until P / P0 reaches 0.5 and the introduction of lithium vapor is stopped. The lithium vapor in the kettle is adsorbed in the pores of the micron-sized porous carbon negative electrode material to obtain pre-lithiation carbon material.

[0036] 5. The obtained pre-lithiated carbon material was transferred to a coating reactor that had been ventilated with argon three times, the temperature was raised to 900°C, the stirring was set to 50 rpm clockwise, and a mixed gas with an argon: acetylene volume ratio of 7:3 was introduced from the bottom of the coating reactor. The CVD gas phase coating was carried out at a constant temperature for 3.5 hours to obtain a carbon-coated pre-lithiated carbon material.

[0037] 6. The obtained carbon-coated pre-lithiation carbon material and the nano-silicon powder in step 1 are granulated into a silicon-carbon composite material through a vacuum liquid phase coating granulation process. Modified asphalt and stearic acid are used as coating agents, and tar is used as a solvent. The added amount is based on the mass ratio of nano-silicon powder, carbon-coated pre-lithiation carbon material, modified asphalt, stearic acid, and tar of 5:95:4:1:20. The stirring is set to 75 rpm clockwise, and the temperature is programmed to 600°C and kept at a constant temperature for 3.5 h for coating and granulation. Finally, the temperature is programmed to 1000°C under argon protection and carbonized at a constant temperature for 6 h to obtain a silicon-carbon negative electrode material with D50=12 μm.

[0038] Example 2

[0039] 1. Add 5N high-purity polysilicon powder with D50=5 μm and zirconia balls into the zirconia ball mill according to the ball-to-material mass ratio of 3:1, and add anhydrous ethanol of equal mass of polysilicon powder at the same time. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward, and repeat this process. After ball milling, separate the zirconia balls and silicon powder through a sieve to obtain nano-scale silicon powder with D50=100 nm.

[0040] 2. Take high-quality coconut shells and zirconia balls in a ball-to-material mass ratio of 3:1 and add them to the zirconia ball mill. At the same time, add anhydrous ethanol of equal mass to the coconut shells. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then let it stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward. Repeat this process. After ball milling, separate the zirconia balls and coconut shell powder through a sieve to obtain a biomass powder with D50=15 μm.

[0041] 3. The obtained biomass powder was placed in a carbonization furnace, and argon was used as a protective gas. The temperature was raised to 600°C and kept at a constant temperature for 6 hours for carbonization. Then, it was transferred to an activation furnace, water vapor was introduced, the temperature was raised to 1000°C, and the temperature was kept at a constant temperature for 6 hours for activation to obtain a micron-sized porous carbon negative electrode material (D50 = 13 μm, total pore volume 1.5 cc / g, most probable pore diameter 0.55 nm).

[0042] 4. Place the obtained micron-sized porous carbon negative electrode material into a ceramic reactor, evacuate until the relative vacuum gauge shows -0.01 MPa, introduce argon until the relative vacuum gauge shows 1 atmosphere, stop introducing argon, evacuate again until the relative vacuum gauge shows -0.01 MPa, repeat 3 cycles to complete the gas exchange. Raise the temperature to 1200℃, and evacuate the vacuum in the reactor until P / P0 is 10 -4 (P0 is the saturated vapor pressure of lithium), lithium vapor (purity 99.95%) is slowly and intermittently introduced, and P / P0 slowly increases until P / P0 reaches 0.6, and the introduction of lithium vapor is stopped. The lithium vapor in the kettle is adsorbed in the pores of the micron-sized porous carbon negative electrode material to obtain pre-lithiation carbon material.

[0043] 5. The obtained pre-lithiated carbon material was transferred to a coating reactor that had been ventilated with argon three times, the temperature was raised to 900°C, the stirring was set to 50 rpm clockwise, and a mixed gas with an argon: acetylene volume ratio of 7:3 was introduced from the bottom of the coating reactor. The CVD gas phase coating was carried out at a constant temperature for 3.5 hours to obtain a carbon-coated pre-lithiated carbon material.

[0044] 6. The obtained carbon-coated pre-lithiation carbon material and the nano-silicon powder in step 1 are granulated into a silicon-carbon composite material through a vacuum liquid phase coating granulation process. Modified asphalt and stearic acid are used as coating agents, and tar is used as a solvent. The added amount is based on the mass ratio of nano-silicon powder, carbon-coated pre-lithiation carbon material, modified asphalt, stearic acid, and tar of 5:95:4:1:20. The stirring is set to 75 rpm clockwise, and the temperature is programmed to 600°C and kept at a constant temperature for 3.5 h for coating and granulation. Finally, the temperature is programmed to 1000°C under argon protection and carbonized at a constant temperature for 6 h to obtain a silicon-carbon negative electrode material with D50=16 μm.

[0045] Example 3

[0046] 1. Add 5N high-purity polysilicon powder with D50=5 μm and zirconia balls into the zirconia ball mill according to the ball-to-material mass ratio of 3:1, and add anhydrous ethanol of equal mass of polysilicon powder at the same time. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward, and repeat this process. After ball milling, separate the zirconia balls and silicon powder through a sieve to obtain nano-scale silicon powder with D50=100 nm.

[0047] 2. Take high-quality coconut shells and zirconia balls in a ball-to-material mass ratio of 3:1 and add them to the zirconia ball mill. At the same time, add anhydrous ethanol of equal mass to the coconut shells. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then let it stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward. Repeat this process. After ball milling, separate the zirconia balls and coconut shell powder through a sieve to obtain a biomass powder with D50=15 μm.

[0048] 3. The obtained biomass powder was placed in a carbonization furnace, argon was used as a protective gas, the temperature was raised to 600°C, and the carbonization was carried out at a constant temperature for 6 hours; then it was transferred to an activation furnace, water vapor was introduced, the temperature was raised to 1000°C, and the activation was carried out at a constant temperature for 4 hours to obtain a micron-sized porous carbon negative electrode material (D50 = 13 μm, total pore volume 1.5 cc / g, most probable pore diameter 0.55 nm).

[0049] 4. Place the obtained micron-sized porous carbon negative electrode material into a ceramic reactor, evacuate until the relative vacuum gauge shows -0.01 MPa, introduce argon until the relative vacuum gauge shows 1 atmosphere, stop introducing argon, evacuate again until the relative vacuum gauge shows -0.01 MPa, repeat 3 cycles to complete the gas exchange. Raise the temperature to 1200℃, and evacuate the vacuum in the reactor until P / P0 is 10 -3 (P0 is the saturated vapor pressure of lithium), lithium vapor (purity 99.95%) is slowly and intermittently introduced, and P / P0 slowly increases until P / P0 reaches 0.4, and the introduction of lithium vapor is stopped. The lithium vapor in the kettle is adsorbed in the pores of the micron-sized porous carbon negative electrode material to obtain pre-lithiation carbon material.

[0050] 5. The obtained pre-lithiated carbon material was transferred to a coating reactor that had been ventilated with argon three times, the temperature was raised to 900°C, the stirring was set to 50 rpm clockwise, and a mixed gas of argon and acetylene with a volume ratio of 5:5 was introduced from the bottom of the coating reactor. The CVD gas phase coating was carried out at a constant temperature for 3.5 hours to obtain a carbon-coated pre-lithiated carbon material.

[0051] 6. The obtained carbon-coated pre-lithiation carbon material and the nano-silicon powder in step 1 are granulated into a silicon-carbon composite material through a vacuum liquid phase coating granulation process. Modified asphalt and stearic acid are used as coating agents, and tar is used as a solvent. The added amount is based on the mass ratio of nano-silicon powder, carbon-coated pre-lithiation carbon material, modified asphalt, stearic acid, and tar of 6:94:4:1:20. The stirring is set to 100 rpm clockwise, and the temperature is programmed to 500°C and kept at a constant temperature for 4 h for coating and granulation. Finally, the temperature is programmed to 1000°C under argon protection and carbonized at a constant temperature for 6 h to obtain a silicon-carbon negative electrode material with D50=16 μm.

[0052] Comparative Example 1

[0053] 1. Add 5N high-purity polysilicon powder with D50=5 μm and zirconia balls into the zirconia ball mill according to the ball-to-material mass ratio of 3:1, and add anhydrous ethanol of equal mass of polysilicon powder at the same time. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward, and repeat this process. After ball milling, separate the zirconia balls and silicon powder through a sieve to obtain nano-scale silicon powder with D50=100 nm.

[0054] 2. Take high-quality coconut shells and zirconia balls in a ball-to-material mass ratio of 3:1 and add them to the zirconia ball mill. At the same time, add anhydrous ethanol of the same mass as the coconut shells. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then let it stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward. Repeat this process. After ball milling, separate the zirconia balls and coconut shell powder through a sieve to obtain a biomass powder with D50=10 μm.

[0055] 3. The obtained biomass powder was placed in a carbonization furnace, and argon was used as a protective gas. The temperature was raised to 600°C and kept at a constant temperature for 6 hours for carbonization. Then, it was transferred to an activation furnace, water vapor was introduced, the temperature was raised to 1000°C, and the temperature was kept at a constant temperature for 6 hours for activation to obtain a micron-sized porous carbon negative electrode material (D50 = 8 μm, total pore volume 1.5 cc / g, most probable pore diameter 0.55 nm).

[0056] 4. Place the obtained micron-sized porous carbon negative electrode material into a ceramic reactor, evacuate until the relative vacuum gauge shows -0.01 MPa, introduce argon until the relative vacuum gauge shows 1 atmosphere, stop introducing argon, evacuate again until the relative vacuum gauge shows -0.01 MPa, repeat 3 cycles to complete the gas exchange. Raise the temperature to 1200℃, and evacuate the vacuum in the reactor until P / P0 is 10 -4 (P0 is the saturated vapor pressure of lithium), lithium vapor (purity 99.95%) is slowly and intermittently introduced, and P / P0 slowly increases until P / P0 reaches 0.5 and the introduction of lithium vapor is stopped. The lithium vapor in the kettle is adsorbed in the pores of the micron-sized porous carbon negative electrode material to obtain pre-lithiation carbon material.

[0057] 5. The obtained pre-lithiation carbon material and the nano-silicon powder in step 1 are granulated into a silicon-carbon composite material through a vacuum liquid phase coating granulation process. Modified asphalt and stearic acid are used as coating agents, and tar is used as a solvent. The added amount is based on the mass ratio of nano-silicon powder, pre-lithiation carbon material, modified asphalt, stearic acid, and tar of 5:95:4:1:20. The stirring is set to 75 rpm clockwise, and the temperature is programmed to 600°C and kept at a constant temperature for 3.5 h for coating and granulation. Finally, the temperature is programmed to 1000°C under argon protection and carbonized at a constant temperature for 6 h to obtain a silicon-carbon material with D50=16 μm.

[0058] Comparative Example 2

[0059] 1. Add 5N high-purity polysilicon powder with D50=5 μm and zirconia balls into the zirconia ball mill according to the ball-to-material mass ratio of 3:1, and add anhydrous ethanol of equal mass of polysilicon powder at the same time. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward, and repeat this process. After ball milling, separate the zirconia balls and silicon powder through a sieve to obtain nano-scale silicon powder with D50=100 nm.

[0060] 2. Take high-quality coconut shells and zirconia balls in a ball-to-material mass ratio of 3:1 and add them to the zirconia ball mill. At the same time, add anhydrous ethanol of the same mass as the coconut shells. Ball mill under vacuum, rotate forward at 500 rpm for 30 minutes and then let it stand for 5 minutes. After standing, reverse at 500 rpm for 30 minutes, continue to stand for 5 minutes, and then continue to rotate forward. Repeat this process. After ball milling, separate the zirconia balls and coconut shell powder through a sieve to obtain a biomass powder with D50=10 μm.

[0061] 3. The obtained biomass powder was placed in a carbonization furnace, and argon was used as a protective gas. The temperature was raised to 600°C and kept at a constant temperature for 6 hours for carbonization. Then, it was transferred to an activation furnace, water vapor was introduced, the temperature was raised to 1000°C, and the temperature was kept at a constant temperature for 6 hours for activation to obtain a micron-sized porous carbon negative electrode material (D50 = 8 μm, total pore volume 1.5 cc / g, most probable pore diameter 0.55 nm).

[0062] 4. Place the obtained micron-sized porous carbon negative electrode material into a ceramic reactor, evacuate until the relative vacuum gauge shows -0.01 MPa, introduce argon until the relative vacuum gauge shows 1 atmosphere, stop introducing argon, evacuate again until the relative vacuum gauge shows -0.01 MPa, repeat 3 cycles to complete the gas exchange. Raise the temperature to 1200℃, and evacuate the vacuum in the reactor until P / P0 is 10 -4 (P0 is the saturated vapor pressure of lithium), lithium vapor (purity 99.95%) is slowly and intermittently introduced, and P / P0 slowly increases until P / P0 reaches 0.5, when the introduction of liquid lithium is stopped. The lithium vapor in the kettle is adsorbed in the pores of the micron-sized porous carbon negative electrode material to obtain pre-lithiation carbon material.

[0063] 5. The obtained pre-lithiated carbon material was transferred to a coating reactor that had been ventilated with argon three times, the temperature was raised to 900°C, the stirring was set to 50 rpm clockwise, and a mixed gas with an argon: acetylene volume ratio of 7:3 was introduced from the bottom of the coating reactor. The CVD gas phase coating was carried out at a constant temperature for 3.5 hours to obtain a carbon-coated pre-lithiated carbon material.

[0064] 6. Physically mix the obtained carbon-coated pre-lithiated carbon material and the nano-scale silicon powder in step 1, with the mass ratio of the carbon-coated pre-lithiated carbon material to the nano-scale silicon powder being 95:5, to obtain a silicon-carbon material with D50=15 μm.

[0065] The schematic diagram of the structure of the silicon-carbon negative electrode material prepared in the embodiment of the present invention is as follows Figure 1 shown.

[0066] In order to detect the performance of the lithium ion battery negative electrode material of the present invention, the half-cell test method, 18650 steel shell full battery, scanning electron microscope, specific surface area and porosity analyzer were used for testing.

[0067] 1) The half-cell test method is to use the silicon-carbon materials prepared in Examples 1-3 and Comparative Examples 1-2 as negative electrode active materials to prepare slurry, and the slurry ratio is active material: SP: SWCNT: CMC: SBR = 95.6%: 0.5%: 0.1%: 1.5%: 2.3%. The slurry is then coated on copper foil and vacuum dried for 12 h to form a negative electrode sheet. The electrolyte is commercially purchased, the separator is a PE film, and the lithium sheet is the counter electrode. A half-cell is assembled in a glove box. A constant current charge and discharge experiment is carried out in the LAND battery test system. The charge and discharge voltage is limited to 0.005-2 V, and a computer-controlled charge and discharge cabinet is used for data collection and control. Example 1 The charge and discharge curve of the silicon-carbon material half-cell test is shown in the figure. Figure 2 The comparison results of the electrical performance of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.

[0068] Table 1

[0069]

[0070] 2) Cycle tests were performed on Examples 1-3 and Comparative Examples 1-2. The test conditions are as follows:

[0071] Table 2

[0072]

[0073] Cyclic test data comparison Figure 3 As shown, the silicon-carbon materials prepared in Examples 1-3 have higher cycle performance, Example 1 has the best cycle performance, while Comparative Examples 1 and 2 have poor cycle performance. Although Comparative Example 2 has a slightly higher reversible specific capacity, its cycle performance is poor.

[0074] 3) Compare the electron microscope images of the silicon-carbon material of Example 1 and Comparative Example 2. Figure 4-5 As shown, Figure 4 This is an electron microscope image of the silicon-carbon material of Example 1, with nano-silicon particles evenly distributed on its surface. Figure 5This is an electron microscope image of the silicon-carbon material in Comparative Example 2. Its nano-silicon is relatively independent. After being made into a battery electrode, the silicon in the negative electrode is more likely to be pulverized and agglomerated, leading to the collapse of the electrode structure and the peeling of the active material.

[0075] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing silicon-carbon negative electrode materials by pre-lithiation by embedding lithium vapor into pores, characterized in that: The steps include: Step 1: Carbonizing and activating the biomass powder at high temperature to prepare a porous carbon negative electrode material; Step 2: introducing lithium vapor into the porous carbon negative electrode material in step 1 under vacuum and high temperature conditions to obtain a pre-lithiated carbon material; The vacuum and high temperature conditions are as follows: after ventilating with protective gas and evacuating, the temperature is raised to 1000-1400°C, and then the vacuum degree is drawn to P / P0 of 10. -2 -10 -6 , P0 is the saturated vapor pressure of lithium; the lithium vapor is introduced until P / P0 rises to 0.4-0.6 and then the introduction is stopped; Step 3: introducing a carbon source gas and a protective gas under high temperature conditions to coat the surface of the pre-lithiated carbon material obtained in step 2 with hard carbon to obtain a carbon-coated pre-lithiated carbon material; Step 4: mixing the carbon-coated pre-lithiated carbon material obtained in step 3 with nano-scale silicon powder, a coating agent, and a solvent, evacuating the mixture, performing vacuum liquid phase coating and granulation, and finally carbonizing the mixture to obtain a silicon-carbon negative electrode material; The D50 of the nano-scale silicon powder is 50-500 nm; the coating agent includes one or two of modified asphalt and stearic acid; the solvent includes one or more of tar, n-hexane, xylene, and tetrahydrofuran; the mass ratio of nano-scale silicon powder to carbon-coated pre-lithiation carbon material is (3-10):(90-97), the amount of coating agent added is 3%-8% of the total mass of the nano-scale silicon powder and the carbon-coated pre-lithiation carbon material, and the amount of solvent added is 15%-50% of the total mass of the nano-scale silicon powder and the carbon-coated pre-lithiation carbon material.

2. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 1, characterized in that: In step 1, the biomass includes coconut shells and bamboo; the high-temperature carbonization is carbonization at 400-800°C for 4-12 h, and the activation is activation at 800-1000°C by introducing water vapor / carbon dioxide for 2-6 h.

3. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 1, characterized in that: In step 1, the D50 of the porous carbon negative electrode material is 7-15 μm, the total pore volume is 1-3 cc / g, and the most probable pore diameter is 0.4-0.85 nm.

4. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 1, characterized in that: The purity of the lithium vapor is not less than 99.95%.

5. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 1, characterized in that: In step 3, the carbon source gas includes one or more of ethane, propane, ethylene, propylene, and acetylene; the high temperature condition is 800-1000° C., and the reaction time is 2-5 h.

6. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 5, characterized in that: The carbon source gas and the protective gas are mixed and introduced, and the volume ratio of the carbon source gas to the protective gas is (10-50):(50-90); the protective gas is one or more of helium, argon, and neon.

7. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 1, characterized in that: The conditions for vacuum liquid phase coating granulation in step 4 are: stirring at 60-150 rpm, heating to 400-600°C, and maintaining the temperature for 2-4 hours; the conditions for the final carbonization are: heating to 900-1100°C under protective gas protection, and maintaining the temperature for 5-7 hours.

8. The method for preparing silicon-carbon negative electrode material by pre-lithiation by embedding lithium vapor into pores according to claim 1, characterized in that: The D50 of the obtained silicon-carbon negative electrode material is 8-18 μm.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery silicon-carbon anode material

    CN107634208A

  • Preparation method of silicon-carbon negative electrode material for high-compaction-density lithium ion battery

    CN108736007A

  • Lithium metal composite material and modified material thereof, and preparation methods and applications of lithium metal composite material and modified material

    CN114944470A

  • Pre-lithiated silicon-oxygen-carbon material, silicon-oxygen-carbon-graphite composite material and preparation method and application thereof

    CN116262617A

  • Pre-lithiated silicon-based negative electrode material and preparation method thereof, negative electrode and battery

    CN117673287A